Pengaruh Tingkat Ketuaan Daun Terhadap Karakteristik Teh Herbal Matcha Tenggulun (Protium javanicum Burm.F.) - Rohiqi, Hasbi; Yusasrini, Ni Luh Ari; Diah Puspawati, GAK. (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 3 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i03.p03, 2021)
The purpose of this study were to determine the effect of leaf maturity on the characteristics of matcha herbal tea tenggulun leaf and to determine the right level of leaf maturity which can produce matcha herbal tea tenggulun leaf with the best characteristics. This study used a completely randomized design (CRD) with, namely very young, young, a little old and old leaves. The parameters observed in this study included moisture content, ash content, crude fiber content, tannin content, total phenol, total flavonoids, antioxidant activity, color and sensory evaluation which included color, aroma, taste and overall acceptance of matcha herbal tea tenggulun leaf. The results showed that the difference in the level of leaf maturity had a very significant effect on moisture content, ash content, crude fiber content, total phenol, total flavonoids, tannin content, antioxidant activity, color and sensory characteristics including color and overall acceptance. However, the level of leaf maturity had no effect on the aroma and taste of matcha herbal tea tenggulun leaves. Matcha herbal tea tenggulun leaves processed from young leaves has the best characteristics with the criteria of water content of 7.93%, ash content of 7.07%, crude fiber content of 13.95%, total phenol 13.36%, total flavonoids 2.39%, tannin content 14.17% antioxidant activity 79.08%, color with a value of L = 21.35, a = -10.46, b = 14.58 and the sensory characteristics of color, aroma, taste and overall acceptance were rather liked.